Immunological Hallmarks for Clinical Response to BCG in Bladder Cancer - Lim, Chun Jye; Nguyen, Phuong Hoang Diem; Wasser, Martin; Kumar, Pavanish; Lee, Yun Hua; Nasir, Nurul Jannah Mohamed; Chua, Camillus; Lai, Liyun; Hazirah, Sharifah Nur; Loh, Josh Jie Hua; Khor, Li Yan; Yeong, Joe; et al. (Frontiers in Immunology, 2021)
Intravesical Bacillus Calmette-Guerin (BCG) is an effective immunotherapy for non-muscle invasive bladder cancer (NMIBC). However, recurrence and progression remain frequent warranting deeper insights into its mechanism. We herein comprehensively profiled blood and tissues obtained from NMIBC patients before, during and after BCG treatment using cytometry by time-of-flight (CyTOF) and RNA sequencing to identify the key immune subsets crucial for anti-tumour activity. We observed the temporal changes of peripheral immune subsets including NKT cells, central memory CD4+ T cells, CD8+ T cells and regulatory T cells (Treg) during the course of BCG. Gene expression analysis revealed enriched immune pathways involving in T cell activation and chemotaxis, as well as a more diversified T cell receptor repertoire in post-BCG tissues. Moreover, tissue multiplexed-immunofluorescence (mIF) showed baseline densities of non-Treg and CD8+PD-1+ T cells were predictive of response and better recurrence-free survival after BCG. Remarkably, post-BCG tissues from responders were found to be infiltrated with more active CD8+PD-1- T cells and non-Treg CD4+FOXP3- T cells; but increased exhausted CD8+PD-1+ T cells were found in non-responders. Taken together, we identified predictive biomarkers for response and uncovered the post-treatment expansion of exhausted PD-1+CD8+ T cells as key to BCG resistance, which could potentially be restored by combining with anti-PD-1 immunotherapy.